POZ/BTB and AT-hook-containing zinc finger protein 1 (PATZ1) inhibits endothelial cell senescence through a p53 dependent pathway - Cho, J H (Nature Publishing Group, 2012)
Vascular cell senescence, induced by the DNA damage response or inflammatory stress, contributes to age-associated vascular disease. Using complementary DNA microarray technology, we found that the level of POZ/BTB and AT-hook-containing zinc finger protein 1 (PATZ1) is downregulated during endothelial cell (EC) senescence. PATZ1 may have an important role as a transcriptional repressor in chromatin remodeling and transcription regulation; however, the role of PATZ1 in EC senescence and vascular aging remains unidentified. Knockdown of PATZ1 in young cells accelerated premature EC senescence, which was confirmed by growth arrest, increased p53 protein level and senescence-associated β-galactosidase (SA-β-gal) activity, and repression of EC tube formation. In contrast, overexpression of PATZ1 in senescent cells reversed senescent phenotypes. Cellular senescence induced by PATZ1 knockdown in young cells was rescued by knockdown of p53, but not by knockdown of p16(INK4a). PATZ1 knockdown increased ROS levels, and pretreatment with N-acetylcysteine abolished EC senescence induced by PATZ1 knockdown. Notably, PATZ1 immunoreactivity was lower in ECs of atherosclerotic tissues than those of normal arteries in LDLR(−/−) mice, and immunoreactivity also decreased in ECs of old human arteries. These results suggest that PATZ1 may have an important role in the regulation of EC senescence through an ROS-mediated p53-dependent pathway and contribute to vascular diseases associated with aging.